ASSESSING TAXPAYER BEHAVIOR TOWARD PBB OBLIGATIONS: EVIDENCE FROM KENDAL - Siti Asnida; Parasdya Pandhu Andanawarih; Arum Pujiastuti (JOB: Journal of Organizational Behavior, 2025)
This study aims to analyze the influence of taxpayer awareness, tax knowledge, income level, service quality, and tax sanctions on taxpayer compliance in paying Land and Building Tax (PBB) in Kendal Regency. A quantitative research method was employed using primary data collected through questionnaires. The sample consisted of 100 respondents. The analysis tool used was SmartPLS with the Structural Equation Modeling (SEM) method. The results showed that taxpayer awareness and income level have a positive and significant effect on taxpayer compliance, while tax knowledge, service quality, and tax sanctions do not have a significant influence on taxpayer compliance